Technology adoption, its impact and determinants: the case of soybean in Madhya Pradesh - Purushottam Sharma; B U Dupare; Ram Manohar Patel (Agricultural Economics Research Review, 2023)
There has been a rapid growth in soybean production in India. Most of it came from area expansion and little from yield improvements. In this paper, we assess the adoption of improved soybean technologies, their effects on yield, and the factors determining their adoption. The findings show that adoption of improved technologies does improve crop yield and farm profit, but their adoption largely remains confined to economically well-off, better-informed, educated large farmers. This implies a need for strengthening linkages between research and extension systems for widespread adoption of improved technologies and cropping practices.